Study on apoptosis effect of human breast cancer cell MCF-7 induced by lycorine hydrochloride via death receptor pathway - Yubin Ji; Miao Yu; Zheng Qi; Di Cui; Guosong Xin; Bing Wang; Weiling Jia; Lin Chang (Elsevier, 2017)
As research was conducted on the early apoptosis of human breast cancer cell MCF-7 caused by lycorine hydrochloride and the expression of the related apoptosis proteins. The early-period apoptosis rate of human breast cancer cell MCF-7 was tested with the AnnexinV/PI double staining and flow cytometry. The Western Blotting method was also used to detect the protein expression conditions of Fas, FasL, Caspase-8 and Bid. The results showed that the higher the dose, the higher the rate of apoptosis and that the rate of apoptosis was dependent on the dose; the relative protein activity of Fas, FasL, Caspase-8 and bid gradually rose with the increase of lycorine dosage and the activities revealed certain dose-independence. Results showed that lycorine hydrochloride could induce the apoptosis of human breast cancer cell MCF-7 through the death receptor pathway. Keywords: Lycorine hydrochloride, MCF-7, Death receptor pathway, Apoptosis